Policy Network in Implementing the Green Open Space in Luwu Timur - Fildayani, Fildayani; Fatmawati, Fatmawati (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
In the Luwu Timur district, green open space or RTH development is typically focused in Malili district's capital, making it difficult for residents of rural areas to access it. The public's lack of involvement in the design and management of RTH, as well as its significance and advantages for the environment and general well-being, are not well known. Determining the scope of the policy network amongst stakeholders in the Open Green Space implementation is the achievement of this study. Qualitative research methodology is applied; thus, methods of gathering data include documentation, library research, interviews, and observations. Among the steps in data analysis are data reduction, data grouping, data interpretation, and conclusion formulation. The study's findings indicate that the local government of Luwu East, DLH, PUPR Service, PT CLM, PT Vale, PT Pegadaian, and Bank of Sulselbar are the official agents in the policy network. While each stakeholder has contributed initiatives to support the development of Green Open Space (RTH) in Luwu Timur District, the efficiency of the policy network remains subject to further assessment based on clearly defined performance indicators. The Bupati Luwu East decision was the foundation for the network's SK No. 200/D-10/V/Year 2022 structure, although it lacked specifics about roles and responsibilities.